Examining the ability of the Cancer and Aging Research Group tool to predict toxicity in older men receiving chemotherapy or androgen‐receptor–targeted therapy for metastatic castration‐resistant prostate cancer. Issue 14 (2nd April 2021) - Alibhai, Shabbir M. H.; Breunis, Henriette; Hansen, Aaron R.; Gregg, Richard; Warde, Padraig; Timilshina, Narhari; Tomlinson, George; Joshua, Anthony M.; Hotte, Sebastien; Fleshner, Neil; Emmenegger, Urban
Abstract : BACKGROUND: Because multiple treatments are available for metastatic castrate‐resistant prostate cancer (mCRPC) and most patients are elderly, the prediction of toxicity risk is important. The Cancer and Aging Research Group (CARG) tool predicts chemotherapy toxicity in older adults with mixed solid tumors, but has not been validated in mCRPC. In this study, its ability to predict toxicity risk with docetaxel chemotherapy (CHEMO) was validated, and its utility was examined in predicting toxicity risk with abiraterone or enzalutamide (A/E) among older adults with mCRPC. METHODS: Men aged 65+ years were enrolled in a prospective observational study at 4 Canadian academic cancer centers. All clinically relevant grade 2 to 5 toxicities over the course of treatment were documented via structured interviews and chart review. Logistic regression was used to identify predictors of toxicity. RESULTS: Seventy‐one men starting CHEMO (mean age, 73 years) and 104 men starting A/E (mean age, 76 years) were included. Clinically relevant grade 3+ toxicities occurred in 56% and 37% of CHEMO and A/E patients, respectively. The CARG tool was predictive of grade 3+ toxicities with CHEMO, which occurred in 36%, 67%, and 91% of low, moderate, and high‐risk groups ( P = .003). Similarly, grade 3+ toxicities occurred among A/E users in 23%, 48%, and 86% with low, moderate, and high CARG risk ( P < .001). However, it was not predictive of grade 2 toxicities with either treatment. CONCLUSIONS: There is external validation of the CARG tool in predicting grade 3+ toxicity in older men with mCRPC undergoing CHEMO and demonstrated utility during A/E therapy. This may aid with treatment decision‐making. Abstract : In a prospective observational multicenter study, the Cancer and Aging Research Group tool was able to predict older men at low (36%), moderate (67%), and high risk (91%) of grade 3+ toxicity with chemotherapy for metastatic castration‐resistant prostate cancer. The same tool was able to identify men at low (23%), moderate (48%), and high risk (86%) of grade 3+ toxicity with abiraterone or enzalutamide.